2010
DOI: 10.1002/cncr.25681
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden and performance status in a population‐based cohort of ambulatory cancer patients

Abstract: BACKGROUND. For ambulatory cancer patients, Ontario has standardized symptom and performance status assessment population-wide, using the Edmonton Symptom Assessment System (ESAS) and Palliative Performance Scale (PPS). In a broad cross-section of cancer outpatients, the authors describe the ESAS and PPS scores and their relation to patient characteristics. METHODS. This is a descriptive study using administrative healthcare data. RESULTS. The cohort included 45,118 and 23,802 patients' first ESAS and PPS, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(149 citation statements)
references
References 50 publications
10
133
2
4
Order By: Relevance
“…The study focused on pain and shortness of breath because they are prevalent in patients with lung and breast cancer and have been well studied using ESAS in other research. [13][14][15][16][17] Of note, in Ontario, unlike in the United States, cancer pain is not measured as a fifth vital sign or as part of routine care. 18 Cancer diagnoses were taken from the cancer center's electronic administrative database.…”
Section: Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study focused on pain and shortness of breath because they are prevalent in patients with lung and breast cancer and have been well studied using ESAS in other research. [13][14][15][16][17] Of note, in Ontario, unlike in the United States, cancer pain is not measured as a fifth vital sign or as part of routine care. 18 Cancer diagnoses were taken from the cancer center's electronic administrative database.…”
Section: Design and Settingmentioning
confidence: 99%
“…Previous research showed that ESAS scores in the Ontario cancer population were heavily skewed toward 0, with approximately half of ESAS assessments reporting 0 scores for pain and shortness of breath, respectively, and approximately 10% reporting scores of 7-10. 17 Following methods used in prior research, the ESAS symptoms were categorized into four categories of severity: none (0 score), mild (1 to 3 score), moderate (4 to 6 score) and severe (7-10 score), where scores of Ͼ 4 indicate clinically significant symptom issues. 24,25 To ensure adequate sample size in each of the ESAS categories by cancer type and symptom, we chose a stratified sampling method.…”
Section: Sampling Strategy and Chart Reviewsmentioning
confidence: 99%
“…Most patients diagnosed with cancer will receive treatment, and patients undergoing treatment experience a multitude of symptoms, including fatigue, pain, difficulty breathing, nausea, appetite loss, and unintentional weight change (2)(3)(4)(5). These symptoms can negatively impact one's ability to complete treatment as well as one's quality of life during and after treatment (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it aims to enhance quality of life at the end of life (eol) 1 . Without effective health care interventions, many cancer patients have uncontrolled symptoms, poor quality of life, and unnecessary suffering [2][3][4][5][6][7][8][9] . The literature suggests that, over time, cancer care is becoming more aggressive near the eol 10,11 .…”
Section: Introductionmentioning
confidence: 99%